KARAKTERISTIK MINERALISASI CEBAKAN AU±LOGAM DASAR DI TAMILOUW – HAYA, PULAU SERAM, MALUKU: MINERALIZATION CHARACTERISTIC OF AU±BASE METAL DEPOSIT AT TAMILOUW - HAYA, SERAM ISLAND, MALUKU - Herfien Samalehu; Arifudin Idrus; Nugroho Imam Setiawan (Buletin Sumber Daya Geologi, 2023)
The research area is located in the southern part of Seram Island, Maluku, which is at an elevation of 3 to 675 meters above sea level; is composed of metapelites to low-grade metamorphic rocks, coralline limestone and alluvial deposits. The purpose of this investigation is to study geological control, mineralization characteristics and ore geochemistry of Au±basemetal deposit in Tamilouw – Haya. Investigation activities began with literature review, field investigations for sampling, geological mapping, alteration & mineralization and laboratory analysis which including polish sections and ore geochemistry (FA/AAS). Based on the results of investigation, it shows that mineralization in Tamilouw - Haya is associated with 3 type of veins, namely quartz veins (V1) that parallel to the foliation plane (concordant), quartz veins that cutting through foliation plane (V2) and third generation veins (V3) are quartz ±carbonate veins associated with breccia - stockwork and formed at the end of veins formation. Massive texture is found in most of the veins, especially those with relatively large dimensions. Vein filling minerals are dominated by quartz, sulfide minerals and precious metals while dominant sulfide veins consist of pyrite and arsenopyrite. Metal sulfide mineralizations at Tamilouw – Haya are pyrite, gold, chalcopyrite, sphalerite, galena, pyrhotite, tetrahydrite, tenantite, marcasite, arsenopyrite, sinabar, kalininite and realgar. Gold grades reaching 0.006 to 7.45 ppm.